Crescimento e acúmulo de nutrientes em couve-flor Verona - Takeishi, Juliana [UNESP]; Cecilio Filho, Arthur Bernardes [UNESP]; de Oliveira, Paulo Roberto (Universidade Federal de Uberlândia (UFU), 2009)
This work consisted in an experiment installed at Unesp, Campus of Jaboticabal, from January to May 2006 and the objective was to evaluate dry matter accumulated and nutrients by cauliflower, hybrid Verona, during the cycle. The experimental design was randomized blocks, in plots subdivided on the time, with three replications. The plants were sampled at 30, 45, 60, 75, 90, 105 and 120 days after sowing (DAS), and were evaluated: number of leaves, stem length, stem and curd diameter, leaf area, stem, leaves and curd dry matter and accumulate of nutrients. The cauliflower growth had four different phases. In the first one, from 0 to 30 DAS, was correspondent of the period from sowing to transplant. In the second phase, from 30 to 75 DAS, the dry matter accumulated in leaves and stem were small in comparison with the total. The third growth phase, from 75 to 97 DAS, was characterized with great dry matter accumulated, increase in the number of leaves and leaf area. This phase ended with visualization of the curd, and was the beginning to the fourth phase, from 97 to 120 DAS. In the culture estimated in 25,000 plants/ha and productivity of 25.2 t ha(-1) the accumulated quantities with of N, P, K, Ca, Mg and S were, corresponding to, 224.5; 54; 156; 136; 21.75; 63.5 kg ha(-1) and 714.8; 270; 236.7 and 33.3 g ha(-1), corresponding to Fe, Mn, Zn and Cu.

Um experimento foi instalado em campo, na Unesp, Campus de Jaboticabal, de janeiro a maio de 2006, e teve como objetivo quantificar o acúmulo de massa seca e de nutrientes pela couve-flor (Brassica oleracea var. botrytis), híbridoVerona, ao longo do ciclo. O delineamento experimental foi o de blocos casualizados, em parcelas subdivididas no tempo, com três repetições. As plantas foram amostradas aos 30, 45, 60, 75, 90, 105 e 120 dias após a semeadura (DAS), sendo avaliados: número de folhas, comprimento do caule, diâmetro do caule e da inflorescência, área foliar, massa seca (MS) de folhas, do caule e da inflorescência e acúmulo de nutrientes. O crescimento da couve-flor foi caracterizado por quatro fases: a primeira, de 0 a 30 DAS, correspondente ao período da semeadura ao transplante; a segunda de 30 a 75 DAS, quando o acúmulo de MS de folhas e caule foi pequeno em relação ao total. A terceira fase, de 75 a 97 DAS, foi caracterizada por grande acúmulo de MS, aumento no número de folhas e na área foliar e foi encerrada com a visualização da inflorescência, que marcou o início da quarta fase, de 97 a 120 DAS. Na cultura com 25.000 plantas por hectare e produtividade de 25,2 t ha-1, as quantidades acumuladas de N, P, K, Ca, Mg e S, foram, respectivamente, 224,5; 53,9; 156; 137,6; 21,8; 63,4 kg ha-1 e de 714,8; 270; 236,7 e 33,3 g ha-1, respectivamente para Fe, Mn, Zn e Cu.
Growth and accumulation of nutrients on cauliflower, hybrid Verona
Keywords: Brassica oleracea var. botrytis; Mineral nutrition; Extraction; Nutrient uptake